From Power-over to Power-to: Power Relations of Women in Hansberry’s A Raisin in the Sun - Saravia Vargas, José Roberto (2012)
Because of binary oppositions shaping Western thought, power has been traditionally understood as male domination or as an unevenly distributed social resource between genders. However, an analysis of the power relationships of the three women in Lorraine Hansberry’s A Raisin in the Sun in the light of Derrida’s thought shows that these notions do not take into account the dynamism and complexity of power relations and hints to the establishment of a new idea of power: transformative power.